Optimal R-SFCL Location in Power Grid - Gour, Abhay Singh (Techniques and Innovation in Engineering Research Vol. 9, 2023)
Increased demand of power generation capacity in distributed electrical power systems has led to an increase in fault current levels exceeding the maximum designed short-circuit ratings of the switchgear. In addition an unbalance in voltage level is also observed during fault owing to the integration of AC and DC micro grids consisting of wind and photovoltaic farms. Resistive type Superconducting Fault Current Limiter (R-SFCL) could be the best solution to suppress the excessive fault current problems and also to reduce voltage instability by improving the rise rate of the transient recovery voltage in Smart grids. However, the latest concern in such applications is about the optimum location of R-SFCL. In this work, we have modeled a HTS based R-SFCL using E-J characteristics of the superconductor and implemented it at various key locations in a smart grid. A Graphical User Interface (GUI) of MATLAB is developed to evaluate the effectiveness of the proposed method on an IEEE benchmarked four-machine two-area test system. Three phase faults of different ratings are studied with and without SFCL at various key points of the smart grid, monitoring the power flows. Such studies on optimum location of SFCL are important to maximize the effectiveness of fault mitigation in an extended network of Power Grid.